Visualization of CSR in the Cigarette Industry: Crafted Imagery, Vague Reality - Masniatul Aulia; Sri Pujiningsih; Dhika Maha Putri (Universitas Negeri Malang, 2024)
Purpose:The objective of this research is to analyze CSR photos in annual reports of the cigarette industry in Indonesia based on the semiotic perspective of Barthes.Method: The visual content analysis approach was used to analyze 374 photos of CSR activities from the three largest cigarette companies in Indonesia.Findings: The usage of photos of CSR activities in the annual reports from the cigarette industry has increased from year to year. The economic and social categories were more disclosed in CSR photos, while the environmental category was relatively less disclosed. The denotative meaning of the photos is as images of company philanthropy and responsibility. The connotative meaning of the photos is to improve the image and blur out the negative impact of the cigarette industry.Originality/Value:The research on visualizing CSR activities in the cigarette industry through the Barthes theory viewpoint is the first of its kind.